Reaction of rice cultivars/lines to Fusarium sheath rot - R.K. TOMBISANA DEVI, N. IBOTON SINGH and (Indian Phytopathology, 2002)
During 1989-95, 92 rice cultivars collected in Hyderabad, Andhra Pradesh, India, were tested for their susceptibility to F. graminearum [Gibberella zeae], F. moniliforme [G. fujikuroi] and F. avenacea [G. avenacea]. Of the cultivars, 23 were highlyresistant and 34 were resistant to all 3 pathogens.